Human development and political violence - Daiute, Colette (Cambridge University Press, 2010)
Machine generated contents note: 1. Beyond the youth gap in understanding political violence; 2. Youth and society work together; 3. Living history; 4. From frozen narratives to critical narrating; 5. Power genres; 6. Sociobiographies; 7. Human development in conflict